Teaching Factory Learning Program at Telkom Malang Vocational High School During the Pandemic - Maula, Putrinda Inayatul; Patmanthara, Syaad; Elmunsyah, Hakkun (Fakultas Teknik Universitas Negeri Malang, 2021)
Teaching factory is a learning concept that adapts the learning conditions in school to those in the industry. But the problem in vocational education today is the lack of absorbed practicum learning caused by the Covid-19 pandemic. Therefore, the focus of this research is the teaching factory learning program at Telkom Malang Vocational High School (TMVHS) during the pandemic. This research method uses a qualitative approach. The location of this research is in TMVHS. The results from the study showed that the preparation carried out by TMVHS was done by finding an industry that was following the competence of students' expertise as partners. The implementation of the teaching factory at TMVHS is the teacher becomes the primary instructor in helping students because learning is completely done online. In addition, there are inhibitory factors during the teaching factory learning process, especially in the pandemic season, namely reduced interaction between students and industry. But these inhibitory factors can be overcome by students who have the enthusiasm and high learning motivation.